Diversification of export markets: A literature review - Guzmán Valle, María (2024)
This research examines the pivotal role of export market diversification in promoting sustainable economic growth. The primary objective is to analyze how expanding trade activities into new international markets can mitigate dependence on a limited number of trade partners, thereby enhancing economic stability and resilience to global economic fluctuations. The methodology involves a comprehensive literature review and empirical analysis using a range of econometric techniques to evaluate the impacts of diversification on economic performance. Key findings highlight that countries with diversified export markets exhibit greater economic stability, reduced volatility in export revenues, and enhanced capacity to cope with external shocks. The results demonstrate a correlation between export diversification and economic growth, supported by increased innovation, competitiveness, and access to a wider range of trade opportunities. Furthermore, the study identifies significant challenges in implementing diversification strategies, such as infrastructural deficiencies, regulatory differences, and the necessity for technological advancement. In conclusion, the research underscores the importance of export diversification as a strategic imperative for long-term economic stability and growth. It recommends adopting coordinated trade policies, investing in infrastructure, and fostering innovation to overcome barriers and fully leverage the benefits of diversified export markets. These measures are crucial for developing sustainable and competitive economies capable of withstanding global economic uncertainties.